2020
DOI: 10.3389/fpsyt.2020.00466
|View full text |Cite
|
Sign up to set email alerts
|

Panic Disorder as Unthinkable Emotions: Alexithymia in Panic Disorder, a Croatian Cross-Sectional Study

Abstract: Objectives: Previous research on alexithymia has led to controversy over its prevalence in panic disorder. The aim of this study was to assess the difference in the prevalence of alexithymia in panic disorder and other anxiety disorders. Design and Methods: We performed a cross-sectional study on a sample of 71 patients diagnosed with panic disorder and 113 patients diagnosed with other anxiety disorders; both groups were 18-50 years old. Primary outcome was the 20-item Toronto Alexithymia Scale (TAS) score. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 78 publications
1
9
0
Order By: Relevance
“…According to the stress-alexithymia hypothesis, the lacking emotional awareness leads to ineffective coping, which prolongs the exposure to stressors and predisposes to mental health problems ( Martin and Pihl, 1985 ). In line with this, previous research has found significant associations between alexithymia and post-traumatic stress symptoms (PTSS), depression and anxiety symptoms ( Frewen et al, 2008 ; Honkalampi et al, 2000 ; Marchesi et al, 2005 ; Tolmunen et al, 2010 ; Šago et al, 2020 ). More specifically, alexithymia has been found to moderate the association between number of traumatic experiences and PTSS ( Park et al, 2015 ).…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…According to the stress-alexithymia hypothesis, the lacking emotional awareness leads to ineffective coping, which prolongs the exposure to stressors and predisposes to mental health problems ( Martin and Pihl, 1985 ). In line with this, previous research has found significant associations between alexithymia and post-traumatic stress symptoms (PTSS), depression and anxiety symptoms ( Frewen et al, 2008 ; Honkalampi et al, 2000 ; Marchesi et al, 2005 ; Tolmunen et al, 2010 ; Šago et al, 2020 ). More specifically, alexithymia has been found to moderate the association between number of traumatic experiences and PTSS ( Park et al, 2015 ).…”
Section: Introductionsupporting
confidence: 67%
“…According to this hypothesis, alexithymic individuals would lack effective emotion regulation and coping due to their impaired emotional awareness and expression, and thus, experience prolonged stress-responses. Numerous studies have reported findings supporting the link of alexithymia to stress-related disorders; for example, it has been found to be associated with depression, anxiety, panic disorder, and cardiovascular disease ( Honkalampi et al, 2000 ; Marchesi et al, 2005 ; Tolmunen et al, 2010 ; Šago et al, 2020 ). Our study provides further evidence of alexithymia as a factor moderating the mental health influences of an uncontrollable event and thus contributing to the cumulative stress load over time.…”
Section: Discussionmentioning
confidence: 99%
“…Depression, anxiety and alexithymia were only assessed by self-report instruments, not by a structured interview. TAS-20 is, however, extensively used in research, and evidence collected for 26 years supports that the scale adequately measures the alexithymia construct ( 3 , 8 , 9 , 11 , 14 , 17 , 18 , 52 ). HADS has also shown high validity for assessing symptoms of depression and anxiety both at an individual and a collective level ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alexithymia was assessed by Toronto Alexithymia Scale-20 items (TAS-20) and alexithymia was defined as ≥ 61 points ( 3 , 8 , 9 , 11 , 12 , 14 , 15 , 17 , 18 , 50 52 ). TAS-20 has a three-factor structure with three subscales, “Difficulty Identifying Feelings” (DIF), “Difficulty Describing Feelings” (DDF) and “Externally Oriented Thinking” (EOT) ( 50 , 51 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation